ULAKBİM Cahit Arf Bilgi Merkezinde Belge Sağlamanın Maliyet Analizi - Yurdagül Ünal (Türk Kütüphaneciliği)
This study aims to review the document delivery requests submitted to the Cahit Arf Information Center, Document Delivery Services Unit of the National Academic Network and Information Center (ULAKBIM). It aims to determine which one is more economic and dispatch in terms of the length of time (in days) it takes to fill a request and the unit cost of supplying requests from printed journals and electronic ones. We tracked the data with regards to document delivery requests that were submitted to the Unit for the year 2000 on October and November. Information (labour cost, corrective maintenance, cleaning, communication, etc.) was obtained from the Center to calculate the unit cost. In order to calculate the unit cost, the cost types such as labour cost, raw product and general cost were identified and the total cost was divided to the total number of document delivery request. The unit cost of supplying an article in the year 2000 was found as about 3 million Turkish Liras (According to the Consumer Price Index of September 2004, the unit cost of a supplied document was 8.690.541 Turkish Liras). From submission to the mailing of the document, it took a total of 15 days to fill a document delivery request. Since the procedure of supplying the electronic or printed documents was not different in the Unit, the length of time and unit cost were almost the same for supplying the documents from printed journals and electronic ones.